The Effect of Competency, Motivation and Organizational Culture on Employee Performance: The Case of Population and Civil Registration Office of Palembang City - Hadinata, Kristian; Rahayu, Sri; Choiriyah, Choiriyah (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine 1) the Effect of Competence, Work Motivation, and Organizational Culture on Employee Performance at the Population and Civil Registration Service of Palembang City. 2) The Effect of Competence on Employee Performance at the Population and Civil Registration Service of Palembang City. 3) The Influence of Work Motivation on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 4) The Influence of Organizational Culture on the Performance of Employees of the Population and Civil Registration Service of Palembang City. This type of research is Associative. The variables used by researchers are Competence, Work Motivation, Organizational Culture, and Performance. The population of this study consisted of all Employees of the Population and Civil Registration Service of Palembang City, and the sample size in the study was 101 employees. The sampling technique used was Proportionate Stratified Random Sampling. The data used in this study are primary data collected through a questionnaire. The data analysis technique used is multiple linear regression, as implemented in the SPSS Program Application. The results of this study indicate that: 1) Competence, Work Motivation, and Organizational Culture have a significant effect on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 2) Competence has a significant effect on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 3) Work motivation significantly influences the performance of employees at the Palembang City Population and Civil Registration Service. 4) Organizational culture significantly influences the performance of employees at the Palembang City Population and Civil Registration Service.